Licitação pública : aspectos que influenciam no processo licitatório - Costa Júnior, José Carlos Pereira da (2016)
One of the public administration principles is the efficient management of public expenditure. This research points out that for public spending efficiency, an efficient management of public bidding, through which the application of much of public resources occurs, is also necessary. For better understanding of the subject, the study searches in organizational theory, concepts on the issue of efficiency in public and private organizations. Supported on the axes of celerity, economic viability, and objectivity in the object description, the work aims to assess the environment of public bidding to verify in its normative framework, elements that account for more efficient results. It is a bibliographical and documentary research analyzed by a variety of combined methods and procedures, (Prodanov and Freitas, 2013), according to the comparative method. This way, we attempt to provide clarity on the issue and assist in the formulation of proposals with the help of the inductive method. The research is of basic nature, although it can be applied, as it seeks to offer the public administrative manager, solutions to the bidding process.